NDRG2 and NDRG4 expression is altered in glioblastoma and influences survival in patients with MGMT-methylated tumors - Kolodziej, Malgorzata; Weischer, Cornelia; Reinges, Marcus H. T.; Uhl, Eberhard; Weigand, Markus A.; Schwarm, Frank P.; Schänzer, Anne; Acker, Till; Quint, Karl; Uhle, Florian; Stein, Marco (Anticancer research, 2016)
Aim: The N-myc down-regulated gene (NDRG) family is a group of genes that have predominantly tumor-suppressive effects. The goal of this study was to investigate the expression of NDRG2 and NDRG4 in surgical specimens of human glioblastoma and in normal brain tissue, and to search for correlations with overall (OS) and progression-free survival (PFS). Materials and Methods: Samples from 44 patients (31 males, 13 females; mean age±SD=57.4±15.7 years) with primary (n=40) or recurrent glioblastoma (n=4) were analyzed by quantitative real-time polymerase chain reaction and immunohistochemistry, with dimensionless semiquantitative immunoreactivity score (IRS), ranging from 0-30] for expression of NDRG2 and NDRG4. Five non-tumorous autopsy brain specimens were used as controls. Results: On the protein level, expression of NDRG2 was significantly down-regulated in glioblastoma (IRS=3.5±3.0 vs. 8.8±3.3; p=0.001), while expression of NDRG4 was significantly up-regulated (IRS=5.4±3.7 vs. 0.75±0.4 vs, p<0.001). There was no statistically significant difference in PFS between a group of 15 patients with glioblastoma with MGMT methylation and enhanced expression of NDRG4 mRNA who were treated with adjuvant radiochemotherapy (temozolomide and 60 Gy) and a group of patients with low expression of NDRG4 mRNA [10 (range=5.5-14.2) months vs. 21 (range=10.7-31.3) months] (p=0.13). Conclusion: Expression of both NDRG2 and NDRG4 genes is significantly altered in glioblastomas. PFS among the patients with glioblastoma with MGMT methylation treated with radiochemotherapy differed significantly in high-expression groups compared to patients without MGMT methylation and without radiochemotherapy (p<0.05).
Accepted February 11, 2016
Gesehen am 24.02.2020